Durable, Washable, and Flexible Conductive PET Fabrics Designed by Fiber Interfacial Molecular Engineering. Issue 11 (23rd August 2016) - Liu, Xuqing; Guo, Ruisheng; Shi, Yuxi; Deng, Libo; Li, Yi
Abstract : Active poly[2‐(methacryloyloxy)ethyl‐trimethylammonium chloride] brushes are grafted from the poly(ethylene terephthalate) surface by surface‐initiated atom transfer radical polymerization, as a platform for copper nanoparticles deposited, which can increase the adhesion between conductive coating and fibers. Abstract : Conductive fibers and fabrics are an essential part of wearable electronics and devices. How to fabricate durable conductive substrate is still a huge challenge to the application and commercialization of wearable electronics. Here an effective and economic process to obtain conductive yarns and fabrics localized copper plating onto synthesized polymers: poly(ethylene terephthalate) (PET) is reported. The active interface is created via plasma treatment to generate active chemical groups on PET substrate, which react with atomic transfer radical polymerization initiator for the following polymerization. The Pd ion entrapped by polymer brushes are then reduced in situ and the Pd 0 species act as a catalytic seed layer for following electroless copper nanoparticles growth on the active interface. Scanning electron microscopy, X‐ray diffraction, field emission gun scanning electron microscopy, and atomic force microscopy are used to characterize the samples in this process, and the copper loading is quantified by weight. The morphology and composition analysis shows that the copper coating on PET fabrics is compact and continuous, which leads to excellent electronic conductivity. The copper coating obtained in this polymer brushes bridged process can pass through the hand washing challenge, and shows excellent adhesion with PET substrate.